Mawangdui-Guidance Qigong Exercise for patients with chronic non-specific low back pain: Study protocol of a randomized controlled trial - Zhang, Guilong; Gao, Liang; Zhang, Di; Li, Hongjian; Shen, Yuquan; Zhang, Zhengsong; Huang, Yong (Frontiers in Neuroscience, 2023)
Abstract Introduction: Worldwide, there is a high frequency of chronic non-specific low back pain (CNLBP), which is a significant public health concern. The etiology is complicated and diverse, and it includes a number of risk factors such as diminished stability and weak core muscles. Mawangdui-Guidance Qigong has been employed extensively to bolster the body in China for countless years. However, the effectiveness of treating CNLBP has not been assessed by a randomized controlled study (RCT). In order to verify the results of the Mawangdui-Guidance Qigong Exercise and examine its biomechanical mechanism, we intend to perform a randomized controlled trial. Methods and analysis: Over the course of four weeks, 84 individuals with CNLBP will be randomly assigned to receive either Mawangdui-Guidance Qigong Exercise, motor control exercise, or medication (celecoxib). EMG data, including muscle activation time, iEMGs, root mean square value (RMS) and median frequency (MF), will be the main results. The Japanese Orthopedic Association Score (JOA), the Mcgill Pain Questionnaire (MPQ), beta-endorphin, and substance P are examples of secondary outcomes. At the start of treatment and four weeks later, all results will be evaluated. Ethics and dissemination: The Sichuan Regional Ethics Review Committee on Traditional Chinese Medicine has given the study approval (Approval No. 2020KL-067). It has also registered at the website of China Clinical Trial Center Registration. The application adheres to the Declaration of Helsinki's tenets (Version Edinburgh 2000). Peer-reviewed papers will be used to publicize the trial's findings. Trial registration number: ChiCTR2000041080